-4(m - 3) - m = m - 6
-4m + 12 - m = m - 6
- 5m + 12 = m - 6
- 5m + 12 + 5m = m - 6 + 5m
12 = 6m - 6
12 + 6 = 6m - 6 + 6
18 = 6m
18 / 6 = 6m / 6
18 / 6 = m
3 = m
- - - - - - - s-
2007-03-24 04:22:03
·
answer #1
·
answered by SAMUEL D 7
·
0⤊
0⤋
-4(m-3)-m = m-6
-4m + 12 - m = m - 6
-4m -m +12 = m - 6
-5m +12 = m - 6
-5m -m = -6 -12
-6m = -18
m = 3
2007-03-24 11:43:21
·
answer #2
·
answered by Mambale S 1
·
0⤊
0⤋
so, distribute the left side of the equal sign.
-4(m-3) - 3 becomes -4m +12 - 3.
Thus, -4m+9 = m-6.
Now, add 4m to both sides.
So, 9 = 5m-6.
Now, add 6 to both sides.
15=5m.
Divide both sides by 5.
m=3.
2007-03-24 11:08:32
·
answer #3
·
answered by berkbelt 2
·
0⤊
0⤋
-4(m-3)-m = m-6
-4(m-3)-m+6=m (add 6 to both sides)
-4(m-3)+6=m+m=2m (add m to both sides)
-4m+12+6=2m (distribute the -4)
-4m+18=2m (12+6=18)
18=2m+4m=6m (add 4m to both sides)
18/6=m (divide by 6 on both sides to solve for m)
m=3
2007-03-24 11:16:03
·
answer #4
·
answered by Larry T 1
·
0⤊
0⤋
-4(m-3)-m = m-6
-4m+12-m =m-6
-5m+12 =m-6
-5m-m = -6-12
-6m = -18
m = -18/-6
m = 3 (minus to be eleminated)
2007-03-24 11:10:38
·
answer #5
·
answered by pritamgola 2
·
0⤊
0⤋
Here is a start.
Distribute the -4 on the left to get
-4m + 12 - m = m - 6
Then combine the m's on the left, subtract m from both sides, and subtract 12 from both sides.
2007-03-24 11:08:04
·
answer #6
·
answered by Anonymous
·
0⤊
0⤋
-4m+12-m=m-6
-5m+12=m-6
12=6m-6
18=6m
m=3 <-- Final answer
2007-03-24 11:08:19
·
answer #7
·
answered by Eve 1
·
0⤊
0⤋
bring'm'on one side of '='
-4m+12-m=m-6
-5m+12-m=-6
-6m=-6-12
-m=-18\6
-m=-3
m==3
2007-03-24 11:13:23
·
answer #8
·
answered by Anonymous
·
0⤊
0⤋
-4m+12-m=m-6
-4m-m-m=-12-6
-6m=-18
-6m/-6=-18/-6
m=3
2007-03-24 11:15:20
·
answer #9
·
answered by freddie 1
·
0⤊
0⤋